2019
DOI: 10.1002/jcp.28657
|View full text |Cite
|
Sign up to set email alerts
|

NK cells: An attractive candidate for cancer therapy

Abstract: Natural killer (NK) cells have significant capability in tumor immune-surveillance. The ability of lyse transformed cells immediately in an antigen-independent manner make them an attractive candidate for cancer cell therapy. Despite employment of NK cells in cancer immunotherapy, clinical trials are faced with serious limitations such as trouble with the penetration of NK cells in tumor sites, limited in vivo persistence, and tumor microenvironment interference. Taken together, the NK-cell cancer therapy is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 131 publications
(236 reference statements)
3
39
0
Order By: Relevance
“…It is well known that immunity decreases with aging and the number of immune cells in cancer patients changes with the development of the disease [25,26]. In the present study, we found that the circulating NK cells were positively correlated to the T and B lymphocytes, which are important immune cells of the human immune system [5][6][7]. Furthermore, we observed that the NK cell percentage was negatively correlated to the patient' age and ALB levels, suggesting that this prognostic indicator may collaborate with other immune indicators in CRC and decrease with aging.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…It is well known that immunity decreases with aging and the number of immune cells in cancer patients changes with the development of the disease [25,26]. In the present study, we found that the circulating NK cells were positively correlated to the T and B lymphocytes, which are important immune cells of the human immune system [5][6][7]. Furthermore, we observed that the NK cell percentage was negatively correlated to the patient' age and ALB levels, suggesting that this prognostic indicator may collaborate with other immune indicators in CRC and decrease with aging.…”
Section: Discussionsupporting
confidence: 60%
“…Among these, the T lymphocytes, B lymphocytes, and natural killer (NK) cells form a vital component of the host antitumor immune response. These cells play crucial roles in the initiation, development, and progression of cancers [5][6][7]. They are also considered as potential targets in immunotherapy and clinical biomarker research [8].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we added NK cells, components of the innate immune branch exerting a cytotoxic action without the need of prior antigen exposure 88,89 . The potential of NK cells in cancer immunotherapy has been pointed out by numerous preclinical studies that showed several attractive features of these cells 90 . Above all, NK cells display an overall safe profile, given by their limited in vivo persistence, the lack of clonal expansion, and the absence of the immune rejection associated with allogeneic transplantation 91 .…”
Section: Discussionmentioning
confidence: 99%
“…Natural killer (NK) cells, which account for 10%–15% of the circulating lymphocytes in the innate immune system, can spontaneously lyse tumor cells without requiring prior sensitization [ 46 ]; therefore, NK cells have unique roles in cancer immune surveillance and clearance [ 47 , 48 ]. Following activation counterbalanced by various receptors, NK cells express activating receptors, including natural cytotoxicity receptors (e.g., NKp30 and NKp44) and Fc-gamma receptors (e.g., CD16), that recognize tumor cells or virus-infected cells [ 49 ].…”
Section: Nanoparticle Facilitates the Killing Ability Of Natural Killmentioning
confidence: 99%